Examination of space/volume requirements for US underground coal mine refuge alternatives - Porter, William L. (Theor Issues Ergon Sci, 2017)
The Mine Safety and Health Administration requires that 1.4 m(2) (15 ft(2)) of floor space is to be provided for each person inside a refuge alternative (RA). However, the amount of floor space needed for a person to reside inside an RA and perform basic tasks is unknown. During testing, participants entered into an RA or a simulated RA of various space/volume configurations and performed several simulated tasks that are representative of the survivability tasks performed within an RA. The results indicate that the floor space requirements were generally adequate for the tasks studied. Certain tasks such as changing scrubber cartridges, using toilets, and moving about the RA were impacted by the minimum height tested (0.6 m). As such, RAs of this height will require critical design consideration as a whole and the supplies provided for use inside of the RA to ensure the ability to use an RA.